L’oppidum arverne de Gondole (Le Cendre, Puy-de-Dôme). Topographie de l’occupation protohistorique (La Tène D2) et fouille du quartier artisanal : un premier bilan - Yann Deberge; Ulysse Cabezuelo; Manon Cabanis; Sylvain Foucras; Magali Garcia; Katherine Gruel; Matthew Loughton; François Blondel; Pierre Caillat (Revue Archéologique du Centre de la France)
Of the three arverni oppida situated in the southern part of the Clermont-Ferrand basin, Gondole is the least known to the general public and to the scientific communities. Unlike her sister sites, Corent and Gergovie, detailed surveys of Gondole have only recently begun, mainly because Gondole lay undiscovered until the early 1990’s.The rescue archaeology trial trenching carried out between 2002 and 2005 led to the discovery of the famous horses and human burial, and marked the beginning of the archaeological research around this site. An open-area excavation conducted outside the Late Iron Age fortification has permitted partial examination of the defenses (ditch) and detailed analysis of an area dedicated to domestic and craft activities (metal working, bone working and ceramic production).In summary, the site is now richly documented and we are able to understand the layout of this large protohistoric occupation that spreads over 70 ha. We are also able to clarify the site’s chronology (La Tène D2).